Development of Wire + Arc additive manufacture for the production of large-scale unalloyed tungsten components - Marinelli, Gianrocco; Martina, Filomeno; Ganguly, Supriyo; Williams, Stewart W. (Elsevier, 2019)
The manufacturing of refractory-metals components presents some limitations induced by the materials' characteristic low-temperature brittleness and high susceptibility to oxidation. Powder metallurgy is typically the manufacturing process of choice. Recently, Wire + Arc Additive Manufacture has proven capable to produce fully-dense large-scale metal parts at relatively low cost, by using high-quality wire as feedstock. In this study, this technique has been used for the production of large-scale tungsten linear structures. The orientation of the wire feeding has been studied and optimised to obtain defect-free tungsten deposits. In particular, front wire feeding eliminated the occurrence of pores and micro-cracks, when compared to side wire feeding. The microstructure, the occurrence of defects and their relationship with the deposition process have also been discussed. Despite the repetitive thermal cycles and the inherent brittleness of the material, the as-deposited structures were free from internal cracks and the layer dimensions were stable during the entire deposition process. This enabled the production of a relatively large-scale component, with the dimension of 210 × 75 × 12 mm. This study has demonstrated that Wire + Arc Additive Manufacture can be used to produce large-scale parts in unalloyed tungsten by complete fusion, presenting a potential alternative to the powder metallurgy manufacturing route.
Keywords: Additive manufacturing; Tungsten; WAAM; Nuclear fusion; Plasma facing material; Microstructure